Genetic variability in microbial eukaryotes reshapes marine biodiversity assessment in the age of amplicon sequencing. - Sarah Trubovitz; Miguel M Sandin; David A Caron (PLoS ONE)
Rapidly improving DNA sequencing technology has revolutionized our ability to efficiently survey the biodiversity of microbial life. We are now equipped to investigate protistan richness and community dynamics on scales that would not have been imaginable with traditional observational methods. However, for most taxa the relationship between DNA sequences and morphologically-defined species is poorly understood, and morphology has remained the cornerstone of taxonomy for centuries. To better utilize the wealth of sequence data being collected, we must understand how it relates to entities such as individuals, populations, and species. Here we use a combined microscopy and sequencing approach to unveil the striking intragenomic and intraspecies genetic variation in one group of ecologically-important marine protists, the polycystine Radiolaria. Long-read 18S rRNA gene amplicon data from 173 isolated and morphologically-identified radiolarians showed that the vast majority (90%) yielded multiple sequence variants per specimen. Furthermore, every morphospecies analyzed displayed a range of different genetic signatures. Intraspecies genetic variability was expressed as specimens having different assemblages of ASVs, different dominant ASVs, or having no ASVs in common with other specimens of the same morphospecies. By integrating morphological and molecular information, we begin to parse the genetic richness of Radiolaria in ocean environments, as well as illuminate relationships between taxa, and their poorly-known life stages. Our findings emphasize the need to account for protists' taxon-specific sequence variability, particularly their intragenomic and intraspecies genetic variation, in interpreting metabarcoding diversity survey data.